Development of Black Pepper Rotary Drum Dryer System - Zainal Abidin, Ana Sakura; Kifli, Mohamad Zulhatta; Jamali, Annisa; Muslimen, Rasli; Ahmadi, Raudhah (International Journal of Integrated Engineering, 2020)
Rotary drum dryer has been identified as hygienic and practical method to dry black pepper. The quality of black pepper is defined based on the chemical properties and moisture content. This research aims to develop a control system for black pepper rotary drum dryer. The dried pepper should meet the specific 12% moisture content while the heating temperature must be kept below 550C. The requirement of 12% moisture content is equivalent to 30% of the remaining weight of the pepper (final weight). The developed system uses Arduino Mega 2560 REV board as a microcontroller.  A type K thermocouple with MAX6675 thermocouple amplifier and S-type load cells (TAS501) with HX711 load cell amplifier are used as input sensor to microcontroller.  The system keeps measuring the current weight until it hit the targeted final weight. Two set of experiments that are using 500 g and 1500 g of pre-treated pepper were conducted to verify the system. As a result, the dryer was successful to work within the desired temperature and it stop operating just after the samples reached 12% of the moisture content. The finding has proven a shorten of drying time from 4 to 7 days when using the traditional method to the current 3 â€“ 5 hours only when using the developed system. Hence, this is an improved method achieved to a quick drying of the black pepper.